P2X(4) Receptors Influence Inflammasome Activation after Spinal Cord Injury - de Rivero Vaccari, Juan Pablo (J Neurosci, 2012)
P2X(4) and P2X(7) are the predominant purinergic P2X receptor subtypes expressed on immune and neural cells. These receptor subtypes traffic between intracellular compartments and the plasma membrane and form protein interactions with each other to regulate ATP-dependent signaling. Our recent studies have shown that P2X(7) receptors in neurons and astrocytes activate NLRP1 inflammasomes, but whether P2X(4) receptors regulate inflammasome signaling is essentially unknown. Here, we demonstrate that P2X(4) receptors are expressed in neurons of the spinal cord. We provide direct evidence that spinal cord injury (SCI) induces an innate inflammatory response that leads to increased caspase-l cleavage and production of IL-1β but not IL-18. Consistent with these findings, P2X(4) knock-out mice showed impaired inflammasome signaling in the cord, resulting in decreased levels of IL-1β and reduced infiltration of neutrophils and monocyte-derived M1 macrophages, resulting in significant tissue sparing and improvement in functional outcomes. These results indicate that P2X(4) receptors influence inflammasome signaling involving caspase-1 activation and IL-1β processing in neurons after SCI. P2X(4) might thus represent a potential therapeutic target to limit inflammatory responses associated with SCI and neurodegenerative disorders.